RBMY, a novel inhibitor of glycogen synthase kinase 3β, increases tumor stemness and predicts poor prognosis of hepatocellular carcinoma. Issue 5 (25th August 2015) - Chua, Huey‐Huey; Tsuei, Daw‐Jen; Lee, Po‐Huang; Jeng, Yung‐Ming; Lu, Jean; Wu, Jia‐Feng; Su, De‐Shiuan; Chen, Ya‐Hui; Chien, Chin‐Sung; Kao, Pei‐Chi; Lee, Chien‐Nan; Hu, Rey‐Heng; et al.
<x xml:space="preserve">Abstract</x> Male predominance of hepatocellular carcinoma (HCC) occurs particularly among young children aged 6‐9 years, indicative of a possible role of the Y chromosome–encoded oncogene in addition to an androgenic effect. The discovery of oncogenic activation of RBMY (RNA‐binding motif on Y chromosome), which is absent in normal hepatocytes but present in male HCC tissues, sheds light on this issue. Herein, we report on a critical hepatocarcinogenic role of RBMY and its ontogenic origin. During liver development, the Ser/Thr phosphorylated RBMY is expressed in the cytoplasm of human and rodent fetal livers. It is then silenced in mature hepatocytes and restricted to scarce expression in the bile ductular cells. Upon hepatocarcinogenesis, a noteworthy increase of cytoplasmic and nuclear RBMY is observed in HCC tissues; however, only the former is expressed dominantly in hepatic cancer stem cells and correlates significantly to a poor prognosis and decreased survival rate in HCC patients. Cytoplasmic expression of RBMY, which is mediated by binding to nuclear exporter chromosome region maintenance 1 and further enriched upon Wnt‐3a stimulation, confers upon tumor cells the traits of cancer stem cell by augmenting self‐renewal, chemoresistance, cell‐cycle progression, proliferation, and xenograft tumor growth. This is achieved mechanistically through increasing Ser9 phosphorylation‐inactivation of glycogen synthase kinase 3β by RBMY, thereby impeding the glycogen synthase kinase 3β–dependent degradation of β‐catenin and eventually inducing the nuclear entry of β‐catenin for the transcription of downstream oncogenes. Conclusion: RBMY is a novel oncofetal protein that plays a key role in attenuating glycogen synthase kinase 3β activity, leading to aberrant activation of Wnt/β‐catenin signaling, which facilitates malignant hepatic stemness; because of its absence from normal human tissues except the testis, RBMY represents a feasible therapeutic target for the selective eradication of HCC cells in male patients. (Hepatology 2015;62:1480–1496)